Fabricating rigid nano-grass layer on Ti6Al4V surface by dealloying for enhanced gingival soft tissue integration - Dongxuan Cai; Meiqi Zhao; Xi Liu; Guangwen Li; Yuqi Zhao; Haochen Wang; Lan Wang; Yide He; Yumei Zhang; Wen Song (Materials & Design)
Fabricating biofavorable nanostructures on Ti6Al4V abutment surface is a promising strategy for improving gingival soft tissue integration (STI) in order to prevent bacteria invasion. Although some structures show both biocompatible and bacterial repulsive, the decades exposure in oral cavity cannot guarantee zero infection. Therefore, developing bioactive and rigid layer is a realistic strategy for clinical scenario. In this study, the dealloying technique was introduced to create nano-grass layer on Ti6Al4V surface by removing Al element. The average size of 30 nm surface could induce the highest and aligned extracellular matrix (ECM) secretion in primary human gingival fibroblasts, accompanied by extensive focal adhesions formation. The epithelial layer in the gingiva-abutment interface was condenser and crosslinked, as indicated by more ECM proteins expression and resistant to HRP invasion. Mechanistically, the cdc42 upregulation and ERK activation account for actin filaments rearrangement and focal adhesions enrichment. Moreover, the grass-like surface showed slight bacteria repulsive property. Thanks to the advantages of dealloying technique, the rigid layer did not show significant damage after conventional scaling by plastic dental scaler. In conclusion, the dealloying technique may be a novel convenient and realistic strategy creating rigid nanoporous surface for both enhancing STI and resistant to physical biofilm removal.